Longitudinal changes in cerebral white matter microstructure in newly diagnosed systemic lupus erythematosus patients. (30th November 2020) - Silvagni, Ettore; Inglese, Francesca; Bortoluzzi, Alessandra; Borrelli, Massimo; Goeman, Jelle J; Revenaz, Alfredo; Groppo, Elisabetta; Steup-Beekman, Gerda M; Huizinga, Tom W J; Ronen, Itamar; de Bresser, Jeroen; Fainardi, Enrico; et al.
Abstract: Objectives: To evaluate longitudinal variations in diffusion tensor imaging (DTI) metrics of different white matter (WM) tracts of newly diagnosed SLE patients, and to assess whether DTI changes relate to changes in clinical characteristics over time. Methods: A total of 17 newly diagnosed SLE patients (19–55 years) were assessed within 24 months from diagnosis with brain MRI (1.5 T Philips Achieva) at baseline, and after at least 12 months. Fractional anisotropy, mean diffusivity (MD), radial diffusivity (RD) and axial diffusivity values were calculated in several normal-appearing WM tracts. Longitudinal variations in DTI metrics were analysed by repeated measures analysis of variance. DTI changes were separately assessed for 21 WM tracts. Associations between longitudinal alterations of DTI metrics and clinical variables (SLEDAI-2K, complement levels, glucocorticoid dosage) were evaluated using adjusted Spearman correlation analysis. Results: Mean MD and RD values from the normal-appearing WM significantly increased over time ( P = 0.019 and P = 0.021, respectively). A significant increase in RD ( P = 0.005) and MD ( P = 0.012) was found in the left posterior limb of the internal capsule; RD significantly increased in the left retro-lenticular part of the internal capsule ( P = 0.013), and fractional anisotropy significantly decreased in the left corticospinal tract ( P = 0.029). No significant correlation was found between the longitudinal change in DTI metrics and the change in clinical measures. Conclusion: Increase in diffusivity, reflecting a compromised WM tissue microstructure, starts in initial phases of the SLE disease course, even in the absence of overt neuropsychiatric (NP) symptoms. These results indicate the importance of monitoring NP involvement in SLE, even shortly after diagnosis.